ENEIAS BETWEEN GODS AND DESTINY: THE CROSSING OF THE MEDITERRANEAN, AN INITIATIVE JOURNEY - Thamos, Marcio [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2022)
In Book III of the Aeneid, the hero tells a series of fantastic episodes he experienced while sailing across the Mediterranean. The aim of the journey is to discover the very purpose of the journey, that is, to know the designs of the destiny reserved for the Trojans and, in the end, to understand clearly what land they could build a new city on. The progressive elucidation of the fatum brings important consequences. It is in the course of this journey that Aeneas matures into a hero with the mission of founding the new Troy.
Keywords: Aeneid; Book 3; fatum; Virgil